Characterization of nitrogen-fixing bacteria isolated from strawberry rhizosphere and their potency to increase seedling growth - FEBBY FITRIYANI; REGINAWANTI HINDERSAH; RINA DEVNITA; SYARIFUL MUBAROK; MASAKAZU NAKAYAMA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fitriyani F, Hindersah R, Devnita R, Mubarok S, Nakayama M. 2025. Characterization of nitrogen-fixing bacteria isolated from strawberry rhizosphere and their potency to increase seedling growth. Biodiversitas 26: 1964-1974. Nitrogen is vital for plant metabolism and strawberry production. Many farmers heavily rely on inorganic fertilizers to meet their nitrogen requirements, which can have adverse environmental impacts. Nitrogen-Fixing Bacteria (NFB) offer an alternative nitrogen source for sustainable strawberry cultivation. This study aimed to isolate and characterize NFB from potted soil and evaluate their potential to enhance strawberry growth and development. NFB was isolated using nitrogen-free media and characterized based on colony and cell morphology, biochemical properties, and growth-promoting abilities. A total of 21 NFB isolates were obtained from the rhizosphere and bulk soil of six-month-old potted strawberries. The isolates were predominantly Gram-negative and exhibited capsule formation. Eleven isolates underwent detailed biochemical characterization, and three were found to fix nitrogen, produce phytohormones, and synthesize exopolysaccharides. Among these, P. megaterium IA-7 exhibited the highest production of nitrogen (4.23 ?mol mL-1g-1h-1), IAA (31.29 ?g mL-1) and gibberellin (21.73 ?g mL-1), while P. aeruginosa 4A-5 demonstrated superior EPS (4.6 g L-1), and cytokinin production (1.47 ?g mL-1). The in-planta experiment revealed that a 1% inoculant significantly increased leaf number (32.5%) and crown diameter (42.44%) compared to the control treatment. These results underscore that the NFB isolated from the strawberry rhizosphere and bulk soil have promising potential as biofertilizers, offering sustainable alternatives to chemical fertilizers that reduce environmental impact and support eco-friendly farming.